PERTURBATIONS OF FRIEDMAN-LEMAITRE-ROBERTSON-WALKER SPACETIMES IN GEROCH-HELD-PENROSE FORMALISM - Novák, J. (Одеські астрономічні публікації, 2016)
We will use Geroch-Held-Penrose formalism for decoupling of quantity dΨ4, which is responsible for tensorial perturbations, in Bianchi equations. We will concentrate on the case, where we eliminate the source terms.